2021
DOI: 10.1177/1054773821995593
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Indicators of Social Position and Self-care Maintenance in Adults with Heart Failure

Abstract: Social determinants of health (SDH) are known to influence health. Adequate self-care maintenance improves heart failure (HF) outcomes. However, the relationship between self-care maintenance and SDH remains unclear. Explore the relationship between sociodemographic indicators of social position and self-care maintenance in adults with HF. This was a secondary analysis of data from a cross-sectional descriptive study of 543 adults with HF. Participants completed the Self-Care of HF Index and a sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…We found that self-reported race was associated with self-care maintenance, with participants of White race (compared with a group that predominantly reported being African American) reporting higher levels. These findings are consistent with a previous study in which self-identified race was associated with self-care maintenance (Baah et al, 2021) but contrasted with another study of self-care in a predominantly African American sample of men with comorbid Type II diabetes and HF (Aga et al, 2019) who had better self-care than others. These findings merit further consideration given evidence of greater risk for adverse HF outcomes and health equity concerns among underrepresented minority groups (Steinberg et al, 2021), including African Americans.…”
Section: Discussionsupporting
confidence: 91%
“…We found that self-reported race was associated with self-care maintenance, with participants of White race (compared with a group that predominantly reported being African American) reporting higher levels. These findings are consistent with a previous study in which self-identified race was associated with self-care maintenance (Baah et al, 2021) but contrasted with another study of self-care in a predominantly African American sample of men with comorbid Type II diabetes and HF (Aga et al, 2019) who had better self-care than others. These findings merit further consideration given evidence of greater risk for adverse HF outcomes and health equity concerns among underrepresented minority groups (Steinberg et al, 2021), including African Americans.…”
Section: Discussionsupporting
confidence: 91%
“…Immigrants with higher income may find it easier to adhere to healthy dietary practices because they are unable to afford the financial costs of healthy groceries (Laaksonen et al, 2003). However, the influence of income on health behaviors is not straightforward because other socioeconomic conditions impact the health of socially marginalized persons (Baah et al, 2019, 2021; Braveman & Gottlieb, 2014; Havranek et al, 2015; Riegel et al, 2017). This characteristic cannot be modified, but screening for income inadequacy may help to identify patients at risk for poor self-care.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, being married, having some college education, and being of Asian race only marginally explained the variance in HF self-care in this study (Baah et al, 2021). To date, studies of the influence of race and gender on HF self-care have consistently yielded inconclusive results (Baah et al, 2021; Graven et al, 2021; Koirala et al, 2018). Although sociodemographic factors may have some impact on HF self-care, other personal factors may be more important in motivating self-care adherence.…”
Section: Introductionmentioning
confidence: 63%
“…In contrast, another study found no association between age, income, and HF self-care (Baah et al, 2021). Moreover, being married, having some college education, and being of Asian race only marginally explained the variance in HF self-care in this study (Baah et al, 2021). To date, studies of the influence of race and gender on HF self-care have consistently yielded inconclusive results (Baah et al, 2021; Graven et al, 2021; Koirala et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation